2013
DOI: 10.1080/19476337.2013.769025
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization and antioxidant properties of baby-leaf watercress produced under organic production system

Abstract: The aim of this study was to evaluate the phytochemical composition and the antioxidant properties of watercress (Nasturtium officinale R. Br., Brassicaceae) produced under organic production system. Fresh baby-leaf watercress samples were collected from local organic farms. High performance liquid chromatography with diode array detection (HPLC-DAD) and high performance liquid chromatography with diode array detection mass spectrometry (HPLC-MS) were used to assess the phytochemical composition, and spectroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 28 publications
1
45
2
Order By: Relevance
“…In contrast, quercetin and kaempferol glycosydes were major phenolics in extracts of watercress leaves (Martínez‐Sánchez et al, ). Aires et al () also reported rutin and isorhamnetin as dominant compounds in watercress extracts.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, quercetin and kaempferol glycosydes were major phenolics in extracts of watercress leaves (Martínez‐Sánchez et al, ). Aires et al () also reported rutin and isorhamnetin as dominant compounds in watercress extracts.…”
Section: Resultsmentioning
confidence: 92%
“…It has been used as medicinal and food crop since old times [1,2]. [1][2][3][4]. Nasturtium has further divided into five species namely, N. officinale, N. microphyllum, N. gambellii, N. africanum, and N. floridanum.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, the hydromethanolic extract exhibited good antioxidant activity when tested with the DPPH scavenging assay and reducing power antioxidant assay. Pearson correlation analysis and primary component analysis confirmed that the antioxidant activities of N. officinale can be accounted for by caffeic acid, rutin, and gluconasturtiin (Aires et al 2013). Hydroethanolic extract of N. officinale and its dichloromethane, ethyl acetate, and butanol fractions exhibited good DPPH scavenging activity and inhibited Fe 2?…”
Section: Nasturtium Officinalementioning
confidence: 63%
“…The major phenolics were chlorogenic acid, quercetin-3-O-rutinoside (rutin), dicaffeoyltartaric acid, and isorhamnetin; the major glucosinolate was gluconasturtiin (Aires et al 2013). In the same study, the hydromethanolic extract exhibited good antioxidant activity when tested with the DPPH scavenging assay and reducing power antioxidant assay.…”
Section: Nasturtium Officinalementioning
confidence: 99%